Effect of vitex smilex on pregnant rats - Nordin, Nor Hafizah Haji (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
The herbal plant Vitex smilex was evaluated for it effects on pregnant albino rats. 54 female rats were used for this study. The rats were divided into control group and treatment group. Extract of the plant was prepared with distilled water by using sohlet apparatus in pharmacology laboratories. The plant extract was administered orally by means of a gavage from day 1 to 7 of pregnancy. Out of 12 rats in each group, 6 were laparotomized under ether anaesthesia on day 1 0 of pregnancy. Both the horns of uterus was observed for number of fetus or resorption site sites and allowed to full term pregnancy. Number of fetus was compared with the number of pups delivered. The remaining 6 rats were used for histological study to confirm the activity of the extract. Result of the study showed that aqueous extract of Vitex smilex did not show efficacy as an antifertility agent. However, late resorbtion was observed in rat, which treated with 1 Omg/kg and 1 OOmg/kg of Vitex smilex extract.